Outcomes of Advanta V12 Covered Stents After Fenestrated Endovascular Aneurysm Repair. (October 2021) - van der Riet, Claire; Schuurmann, Richte C. L.; Verhoeven, Eric L. G.; Zeebregts, Clark J.; Tielliu, Ignace F. J.; Bokkers, Reinoud P. H.; Katsargyris, Athanasios; de Vries, Jean-Paul P. M.
Purpose: Fenestrated endovascular aneurysm repair (FEVAR) is a well-established endovascular treatment option for pararenal abdominal aortic aneurysms in which balloon-expandable covered stents (BECS) are used to bridge the fenestration to the target vessels. This study presents midterm clinical outcomes and patency rates of the Advanta V12 BECS used as a bridging stent. Methods: All patients treated with FEVAR with at least 1 Advanta V12 BECS were included from 2 large-volume vascular centers between January 2012 and December 2015. Primary endpoints were freedom from all-cause reintervention, and freedom from BECS-associated complications and reintervention. BECS-associated complications included significant stenosis, occlusion, type 3 endoleak, or stent fracture. Secondary endpoints included all-cause mortality in-hospital and during follow-up. Results: This retrospective study included 194 FEVAR patients with a mean age of 72.2±8.0 years. A total of 457 visceral arteries were stented with an Advanta V12 BECS. Median (interquartile range) follow-up time was 24.6 (1.6, 49.9) months. The FEVAR procedure was technically successful in 93% of the patients. Five patients (3%) died in-hospital. Patient survival was 77% (95% CI 69% to 84%) at 3 years. Freedom from all-cause reintervention was 70% (95% CI 61% to 78%) at 3 years, and 33% of all-cause reinterventions were BECS associated. Complications were seen in 24 of 457 Advanta V12 BECSs: type 3 endoleak in 8 BECSs, significant stenosis in 4 BECSs, occlusion in 6 BECSs, and stent fractures in 3 BECSs. A combination of complications occurred in 3 BECSs: type 3 endoleak and stenosis, stent fracture and stenosis, and stent fracture and occlusion. The freedom from BECS-associated complications for Advanta V12 BECSs was 98% (95% CI 96% to 99%) at 1 year and 92% (95% CI 88% to 95%) at 3 years. The freedom from BECS-associated reinterventions was 98% (95% CI 95% to 100%) at 1 year and 94% (95% CI 91% to 97%) at 3 years. Conclusion: The Advanta V12 BECS used as bridging stent in FEVAR showed low complication and reintervention rates at 3 years. A substantial number of FEVAR patients required a reintervention, but most were not BECS related.